Tokyo ghoul. Vol. 7 - Ishida, Sui (Viz signature., 2016)
"Kaneki is captured and then tortured by Yamori, one of Aogiri Tree organization's most sadistic members. To survive the interrogation, Kaneki will have to finally surrender to the Ghoul inside him, but if he does, it will change him permanently and push him even further away from being human" -- page 4 of cover.